2013
DOI: 10.1016/j.pmrj.2013.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Bone Marrow Adiposity and Cortical Bone Cross‐Sectional Areas in Men With Motor Complete Spinal Cord Injury

Abstract: After SCI, cortical bone CSA becomes thinner and is associated with greater accumulation of yellow BMA. Yellow BMA is associated with changes in bone CSA and bone mass, as well as increased fat mass, after SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 43 publications
(117 reference statements)
1
18
0
Order By: Relevance
“…Moreover, the bone marrow adipose tissue was inversely related to the bone mineral density and bone mineral content as measured by DXA. This preliminary evidence suggests that there is inverse relationship between increasing bone marrow adiposity and both cortical bone as well as bone mineral density [7] . This may suggest that MSC need to be considered as a therapeutic anatomical target for future interventions to cease the progress in adiposity and osteoporosis after SCI.…”
Section: Bone Marrow Adipose Tissuementioning
confidence: 78%
See 4 more Smart Citations
“…Moreover, the bone marrow adipose tissue was inversely related to the bone mineral density and bone mineral content as measured by DXA. This preliminary evidence suggests that there is inverse relationship between increasing bone marrow adiposity and both cortical bone as well as bone mineral density [7] . This may suggest that MSC need to be considered as a therapeutic anatomical target for future interventions to cease the progress in adiposity and osteoporosis after SCI.…”
Section: Bone Marrow Adipose Tissuementioning
confidence: 78%
“…This differentiation may be very important in providing the appropriate mechanical stimulus necessary for the development of muscle and bone tissue compared to adipose tissues after SCI. Our initial observation showed that persons with motor complete SCI had 2-3 times bone marrow adipose tissue compared to matched able-bodied controls; primarily because of unloading on lower extremities [7] . This is accompanied with 1.5-2 times lower cortical bone CSA in persons with SCI compared to able-bodied controls [7] .…”
Section: Bone Marrow Adipose Tissuementioning
confidence: 96%
See 3 more Smart Citations